Peran Optimisme dalam Memediasi Pengaruh Pendidikan Kewirausahaan terhadap Grit pada Mahasiswa yang Mengikuti Program Wirausaha - Utami, Dian Ratri; Iftayani, Itsna; Setiawan, Budi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The low interest of college graduates in entrepreneurship is a challenge in itself. One of the factors that influences student resilience in entrepreneurship is grit, namely perseverance and consistency in achieving long-term goals. The purpose of this study was to determine whether optimism is a mediator of the influence of entrepreneurship education on grit. This study uses a quantitative approach with a mediation analysis design. The subjects of the study were students who participated in the Student Entrepreneurship Development Program (P2MW) at Muhammadiyah and Aisyiyah Colleges (PTMA) in Former Kedu Residency Area in 2022–2024, with a sample size of 68 respondents. The results showed that entrepreneurship education had a direct and significant effect on student grit (p = 0.012). Optimism acts as a partial mediator in the relationship between entrepreneurship education and grit (p = 0.040), which means that optimism strengthens the influence of entrepreneurship education on grit, but is not the only determining factor. This study contributes to university policies in assisting student entrepreneurship development programs.